The problems of commercial property management practice case study: KB Mall, Kelantan / Syazana Alya Shamsulbadri - Shamsulbadri, Syazana Alya (2023)
Shopping centres in Malaysia have made a significant contribution to the tourism industry's rapid expansion. As a result, business owners and managers should take seriously their responsibilities for the efficient functioning of retail malls. Many of the commercial buildings in Kelantan are in poor condition, and some are even deteriorating as a result of inadequate property management and maintenance. Property management is still unclear, especially in Malaysia where varied approaches are taken there. The first objective is to identify the property management practice for commercial shopping complex. Next, the second objective is to determine the issues of property manager managing the commercial property. The third objective is to propose the effective property management elements in achieving the success of shopping mall, using KB Mall as a case study. In this study, the researcher has adopted a quantitative method by using a Google Form. This research has successful in gathered 156 respondents which means it has achieved the sampling size then will be analyzed by using the SPSS.